Brazilian metropolitan regions: regime change and governance vacuum - Souza, Celina (2005)
The article analyses the political and the institutional features of Brazilian metropolitan regions in relation to (a) the influence of regime change, from authoritarianism to democracy; (b) the changes in the federal system brought about by the 1988 constitution designed to legitimise the new democratic order; and (c) the dynamics of intergovernmental relations. It argues that the institutionalisation of metropolitan regions and the creation of agencies for their management during the military regime became associated with the regime's major negative features-authoritarianism and centralisation -hence influencing future choices and leaving metropolitan governance in a political, institutional, financial and administrative vacuum. - Reproduced.
Keywords: Local government - Brazil; Local government